Srpski - Kajević, Amina (Glasnik Advokatske komore Vojvodine, 2020)
This paper analyzes initiation of the reorganization procedure by comparing the initiation of the "classical" reorganization and initiation of the reorganization in accordance with the prearranged reorganization plan. The analysis of initiating these two types of reorganization will be performed by considering the three elements that crucially affect the initiation of reorganization in a single legal system - when the reorganization procedure is initiated, persons authorized to initiate this procedure and the obligatory content of the reorganization plan. The manner in which these three elements are arranged can significantly influence the quality of the reorganization plan and its successful implementation. The aim of this paper is to analyze the initiation of two types of reorganization in Serbian bankruptcy law by comparing these three elements, as well as to point out some controversial issues that arise when initiating these two proceedings.